Panel : real-time discussions on real-time data processing. (Manning Publications, 2021)
How do streaming experts define 'streaming'? What are their favorite use cases of real-time streaming, and how do they help boost real-time pricing in retail? Why having just a messaging system doesn't mean that you have a streaming system? The main difference between Apache Pulsar and Kafka. The best practices and patterns for data-streaming and messaging.